Effect of Different Solvent on Total Phenolic, Total Flavonoid, and Sun Protection Factor of Belimbing Wuluh (Averrhoa Bilimbi linn.) Fruits Fraction - Ryan Radix Rahardhian (Journal of Global Pharma Technology, 2016)
Ultraviolet (UV) radiation is related with a variety of damaging effects. Averrhoa bilimbi Linn (AB) known as Belimbing Wuluh in Indonesia, it contains phenolic compounds such as flavonoids, where the compound has the potential as a sunscreen. Objective: the study was to determine the Total Phenolic Content (TPC), Total Flavonoid Content (TFC) and investigate Sun Protection Factor (SPF) activity from different solvent for fractionation of AB among N Hexane (NH), Ethyl Acetate (EA), and Water. Methods: TPC, TFC, and Sun SPF were investigated using in vitro assay with spectrophotometric UV-Vis coupled chemometric using principal component analysis (PCA). In this study, TPC was determined using Folin-Ciocalteu reagent, the outcomes were expressed in (mg of gallic acid equivalent (GAE)/g sample), TFC content was determined by colorimetric using AlCl3 methods, the results were expressed in (mg of rutin equivalent (RE)/g sample), and SPF using Dutra calculation. Result:  EA showed the highest SPF (15, 38±1, 3).The similar fraction having the highest TPC (56, 87±1, 5212) mg (RE)/g of EA) and the highest TFC (24, 99±3, 2895) mg (GAE)/g of EA). When principal component analysis (PCA) was applied, high correlation among TFC and SPF activities was found. Conclusion: Hence, AB potential as sun screens.Keywords: Averrhoa bilimbi, Total Flavonoid Content, Total Phenolic Content, Sun Protection Factor, Chemometric.